Predictors of future academic productivity in pediatric otolaryngology fellowship applicants. (June 2022) - Cha, Jeremy; Preciado, Diego; Mann, Hannah; Behzadpour, Hengameh; Chillakuru, Yeshwant; Espinel, Alexandra G.
Abstract: Objectives: To investigate which components of pediatric otolaryngology fellowship applications are more closely predictive of future academic productivity in applicants who go on to complete their fellowship training. Methods: Applications to our institution's ACGME accredited pediatric otolaryngology fellowship program through the SF Match program for the years 2011–2016 were reviewed. Applicant files on record were utilized to extract independent variables including sex, mean USMLE score, residency program Doximity ranking, military experience, number of national honors/awards, AOA status, total number of publications listed on application, number of first author publications listed on application, and AAOHNS Committee involvement. Academic productivity was determined by number of PubMed indexed publications per year, practice setting, and H-index (Scopus). Statistical analysis consisted of multivariate and univariate regression models, with p < 0.05 being considered statistically significant. Results: Multivariate regression showed that USMLE Step 1 and 2 mean score and number of publications listed on application exhibited statistically significant correlations with a higher number of future post fellowship publications per year. Residency program Doximity rank, applicant number of awards and honors, AOA status, and number of first author publications were not predictive of future academic productivity. No statistically significant associations were found between any variables and the faculty position outcome variable. Conclusions: Quantifiable criteria in pediatric otolaryngology fellowship applications, such as number of listed publications and mean USMLE scores are strongly correlated with future academic productivity metrics.